1968
DOI: 10.1136/jcp.21.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injected heparin on platelet levels in man

Abstract: SYNOPSIS Platelets from six normal subjects were labelled with radiochromate and reinfused into their donors. Subsequently, the effect of intravenously injected heparin upon the levels of circulating platelets and platelet radioactivity was studied. Although reductions in platelet counts occurred in three subjects following single injections of 10,000 units, these changes were not reflected in the levels of circulating platelet radioactivity. It is concluded that the alterations in platelet counts observed wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…crease in plasma fibrinogen during heparinization in a patient with primary biliary cirrhosis suggests minimal functional alterations of the hepatocytes which may correspond to their inconspicuous changes on electron microscopy (45). Absence of obvious increase in circulating platelets during heparinization does not militate against the concept of intravascular coagulation because heparinization by itself tends to reduce the platelet level (46)(47)(48)(49)(50).…”
Section: Resultsmentioning
confidence: 99%
“…crease in plasma fibrinogen during heparinization in a patient with primary biliary cirrhosis suggests minimal functional alterations of the hepatocytes which may correspond to their inconspicuous changes on electron microscopy (45). Absence of obvious increase in circulating platelets during heparinization does not militate against the concept of intravascular coagulation because heparinization by itself tends to reduce the platelet level (46)(47)(48)(49)(50).…”
Section: Resultsmentioning
confidence: 99%
“…A number of years ago, several investiga tors reported that heparin resulted in an acute but transient drop in the platelet count in ani mals and sometimes in humans [7][8][9][10][11][12][13], The validity of this observation has been chal lenged, and one group suggested that it might be an artifact due to in vitro aggregation of the platelets caused by the heparin [13], In summary, heparin interacts with plate lets in vitro and this interaction depends pri marily upon characteristics of the heparin preparation.…”
Section: Non-idiosyncratic (Acute) Heparin-platelet Interactionsmentioning
confidence: 99%
“…The Type I or non-immune mediated HIT is a transient, benign, and self-limiting form of thrombocytopenia. In Type I HIT patients, a decrease in platelet count occurs in the first five days of the therapy due to the direct agglutinating impact of heparin on platelets 9,10 .…”
Section: Ijpsr (2017) Volume 8 Issue 8 (Review Article)mentioning
confidence: 99%
“…However, the development of thrombocytopenia in immune-mediated or Type II HIT appears within 5 th to 14 th day of the initiation of heparin therapy 9,11 . In the immunologically mediated HIT condition, the antibodies are directed to heparin/platelet factor 4 (PF4) complexes that are formed during the heparin treatment 3 .…”
Section: E-mail: Drsaldallal@outlookcommentioning
confidence: 99%